PENERAPAN TEKNOLOGI DALAM PENCEGAHAN STUNTING DI UPTD PUSKMAS SUKAMULYA, KECAMATAN CIHAURBEUTI, KABUPATEN CIAMIS: APPLICATION OF TECHNOLOGY IN STUNTING PREVENTION AT SUKAMULYA COMMUNITY HEALTH CENTER UPTD, CIHAURBEUTI DISTRICT, CIAMIS REGENCY - Iskandar, Iqbal Dzulfiqar; Yani Sri Mulyani , Yani Sri Mulyani; Yanti Apriyani, Yanti Apriyani; Imam Amirulloh, Imam Amirulloh; Hendri Mardani, Hendri Mardani; Zidane Dwi Kusuma , Zidane Dwi Kusuma (PADIMAS Jurnal Pengabdian Masyarakat, 2024)
The Sukamulya Health Center UPTD is in Cihaurbeuti District, Ciamis Regency. Precisely on Jl. Raya Panjalu No. 24 Rt.01/Rw.01, Village. Sukamulya, District. Cihaurbeuti, Ciamis Regency, West Java, Indonesia 46262. Where the Sukamulya Health Center UPTD manages 6 villages and 37 posyandu. The problem faced by the Sukamulya Health Center UPTD is the development of an Android-based stunting data collection application in terms of automatic detection in identifying children who are stunted, so that it can speed up data collection and save time. The focus of the objective in discussing this community service activity is to recommend the application of technology in preventing stunting so that detection can be carried out quickly and accurately as well as providing recommendations if a child is affected by stunting with the Artificial Intelligent (AI) feature. with this application, every time a weighing is carried out at the posyandu, a database for monitoring the growth and development of toddlers will be available. The method used in this activity is a training workshop for posyandu cadres by directly practicing how to operate the stunting application that has been developed. The community service strategy implemented includes practical training and the use of technology to increase the accuracy and speed of stunting data reporting.  Significant findings from this activity are the increase in the ability of posyandu cadres to record stunting and provide stunting data with appropriate recommendations through AI, the ability of each posyandu cadre to collect data related to stunting through an Android-based application and provide recommendations automatically if there are indications of stunting, and through features ChatGpt so that Posyandu cadres can ask questions via this column according to problems encountered in the field. In conclusion, the implementation and workshop on operating stunting data collection and monitoring applications based on this Android application can be carried out at the Sukamulya Community Health Center UPTD, with the stunting application that has been developed posyandu cadres can carry out data collection quickly and efficiently and can then report it to the sub-district easily.